Leonardo da Vinci : a memory of his childhood - Freud, Sigmund, 1856-1939 (International library of psychology, 1999)
A reconstruction of Leonardo's emotional life from his earliest years, it represents Freud's first sustained venture into biography from a psychoanalytic perspective, and also his effort to trace one route that homosexual development can take.